Virtual play and real connections: unpacking the impact of rice farming simulation video games - Nishimura, Takeshi; Taguchi, Junko; Kumazawa, Terukazu; Hayashi, Kengo (Frontiers in Computer Science, 2024)
This study investigates how the rice farming simulation video game Sakuna: Of Rice and Ruin affects interest in real-world agriculture and the inclination to start farming amidst Japan’s declining farming population. We surveyed 428 Japanese residents, including not only game players but also those who watch the game live or are merely aware of its existence. We also interviewed an individual who started rice farming after playing the game. The findings indicate that the game successfully stimulates greater interest in agriculture and somewhat motivates players to consider farming, more than just viewers or those who are aware of it. Moreover, individuals with real-life connections to agriculture, such as farming experience or professional connections, were optimistic about the transition from game to reality. The study suggests that rice farming simulation games can foster expectations of developing an interest in agriculture and potentially embarking on farming careers, demonstrating the game’s significant impact beyond entertainment.